Analysis of Production Cost Determination Using Full Costing and Variable Costing Methods as a Basis for Selling Price Determination (Case Study of Santi Karawang Cake SME) - Rodiah Salsabillah Pakaya; Usman Usman; Ayu Rakhma Wuryandini (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to compare the full costing and variable costing methods in determining the cost of goods manufactured for selling prices (a case study of the Santi Karawang Cake SME). This study employed a quantitative descriptive method, utilizing primary and secondary data as sources of information. Secondary data included information on Krawang Cake production, raw material inventory, and Krawang Cake production at the Santi Karawang Cake SME. The data analysis techniques used in this study were the full costing and variable costing methods. These methods are considered relevant in calculating total costs incurred during the production process, which include direct material costs, direct labor costs, and factory overhead costs. The results showed that calculating the cost of goods manufactured using the full costing method yielded higher results than using variable costing. Furthermore, the calculation using the variable costing method resulted in a lower COGS because it only included variable costs, namely raw material costs, direct labor costs, and variable factory overhead costs.